Reprogramming of Urine-Derived Renal Epithelial Cells into iPSCs Using srRNA and Consecutive Differentiation into Beating Cardiomyocytes - Heidrun Steinle; Marbod Weber; Andreas Behring; Ulrike Mau-Holzmann; Christiane von Ohle; Aron-Frederik Popov; Christian Schlensak; Hans Peter Wendel; Meltem Avci-Adali (Elsevier, 2019)
The generation of induced pluripotent stem cells (iPSCs) from patient's somatic cells and the subsequent differentiation into desired cell types opens up numerous possibilities in regenerative medicine and tissue engineering. Adult cardiomyocytes have limited self-renewal capacity; thus, the efficient, safe, and clinically applicable generation of autologous cardiomyocytes is of great interest for the treatment of damaged myocardium. In this study, footprint-free iPSCs were successfully generated from urine-derived renal epithelial cells through a single application of self-replicating RNA (srRNA). The expression of pluripotency markers and the in vitro as well as in vivo trilineage differentiation were demonstrated. Furthermore, the resulting iPSCs contained no residual srRNA, and the karyotyping analysis demonstrated no detectable anomalies. The cardiac differentiation of these iPSCs resulted in autologous contracting cardiomyocytes after 10 days. We anticipate that the use of urine as a non-invasive cell source to obtain patient cells and the use of srRNA for reprogramming into iPSCs will greatly improve the future production of clinically applicable cardiomyocytes and other cell types. This could allow the regeneration of tissues by generating sufficient quantities of autologous cells without the risk of immune rejection. Keywords: self-replicating RNA, reprogramming, iPSCs, urine, renal epithelial cells, cardiomyocytes, regenerative medicine